The Relationship between Civic Education and Active Political Participation of Students - Rasha Al-Ansari; Omar Al-Fahim; Benjamin Zang (Yayasan Adra Karima Hubbi, 2025)
Background. This study explores the relationship between civic education and active political participation among students. As democracy and civic engagement become increasingly essential in modern societies, understanding how education influences political behavior is critical. Civic education aims to provide students with the knowledge, skills, and values necessary to participate effectively in democratic processes. Purpose. The purpose of this research is to examine how civic education impacts students’ attitudes toward political participation and their actual involvement in political activities. Method. This study uses a mixed-method approach, combining quantitative surveys with qualitative interviews. The survey was administered to 300 high school and university students, assessing their understanding of political processes, civic responsibilities, and participation in political activities. The qualitative interviews provided deeper insights into students’ personal experiences and motivations. Results. The results show that students who received more comprehensive civic education demonstrated higher levels of political awareness and were more likely to engage in activities such as voting, attending political meetings, and participating in social movements. Conclusion. The study concludes that civic education plays a significant role in fostering active political participation among students. Integrating civic education into the curriculum can enhance democratic engagement and ensure that future generations are equipped to contribute to the political landscape.